Pre-default and its effect on the performance of the contractual obligation at the debtores expense - عبد الصاحب, علي مطشر; حسن, ماجد مجباس (Journal of Legal Sciences, 2019)
Per- breach of the contract is that the other contractor shall act, act or issue a statement indicating that will not out the performance on time and that such breach may provide the contracting party with the right to damage a range of options in order to remedy such damage, if there is necessity, there is also the possibility of reparation through the performance at the expense of the debtor. This matter is relative according to each law. It is different in English law than in civil laws as the latter lack an integrated regulation of predefault provision. The provisions are detailed.